Dehierarchizing Space: Performer-Audience Collaborations in Two Portuguese Performances of Shakespeare - Rayner, Francesca (2017)
This article addresses the key role of performance space in mediating between cultural locations. It discusses two Portuguese performances of Shakespeare where audiences were invited to become part of the performance and the ways in which this dehierarchization of the performance space framed a cross-cultural encounter between a globalized text and a localized performance context. In Teatro Oficina's 2012 King Lear, both audience and performers sat around a large table in a production which reflected upon questions of individual and collective responsibility in Shakespearean tragedy and in the wider political sphere. In the middle of this performance space hung a large cube onto which the translated text was projected, setting up a spatial tension between text and performance that also foregrounded the translocation of the Shakespearean text to a Portuguese performance context. In Tiago Rodrigues' 2013 By Heart, ten members of the audience were invited onstage to learn Shakespeare's Sonnet 30 " by heart and not by brain." 1 In doing so, Rodrigues emphasized the cultural embeddedness of Shakespearean texts in a wider European cultural context and operated a subtle shift from texts to performance as a privileged repository for the cultural memory of Shakespeare. The article explores how these spatial shifts signaled the possibility of enabling cross-cultural identifications with Shakespeare through performance.